EVALUATION OF THE FACTORS THAT INFLUENCE ON THE QUALITY OF EDUCATIONAL SERVICES IN UKRAINE - Kuznetsova, Nataliia (Continuing Professional Education: Theory and Practice, 2019)
The article describes and identifies the key factors influencing on the quality of educational services rendering in Ukraine and the analytical evaluation has been given to them. The special attention has been focused on the external regulated factors, which have a direct impact on the dynamics of quality indicators in the educational system. There are several ones of them. First, it’s organizational, it means it is doing through the mechanism of the scientific and educational cooperation and collaboration of science with education and business; second, it is a social one – through a system of wages and social payments for employees in the education; third, it is financial – through the mechanism of the state financial planning and management; fourth, it can be an evaluation through the mechanism of the quality control of rendering educational services; and finally, fifth, it is a motivational factor which can be run through a system of continuous, non-finishing education of the pedagogical staff. пах безперервного навчання учасників освітнього процесу. Тільки впровадження комплексних заходів і нових підходів до вирішення існуючих проблем дозволить створити умови для підвищення якості освітніх послуг, що сприятиме поліпшенню якості життя та добробуту населення країни. Частина I ОСВІТОЛОГІЯ – НАУКОВИЙ НАПРЯМ ІНТЕГРОВАНОГО ПІЗНАННЯ НЕПЕРЕРВНОЇ ОСВІТИ 19 To solve this problem of quality educational services rendering in Ukraine, the author has examined the possible ways of its solutions. They are mentioned below. Among them there is development of new forms of cooperation between education and business. Then we must say about improving the system of labor payment and social protection of employees in the educational field through the forming of the new approaches to the estimation of intellectual activity. The next one is the reforming of the educational system itself and the logistics of the educational establishments through the expansion of their legal autonomy and academic freedom. We must mention also improving of the system of quality management education through its institutional reform. The quality of the educational system is impossible also without the development of intra-corporate teaching environment and the bases of professional education continuing of the higher schools pedagogical personnel of professional education by creating the corporate training centers.